2014
DOI: 10.3389/fnagi.2014.00184
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 enhances 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal damage via apoptotic pathway

Abstract: Sirtuins are NAD-dependent protein deacetylases that were shown to have protective effects against different age-related diseases. SIRT2 is a strong deacetylase that is highly expressed in brain. It has been associated with neurodegenerative diseases. MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) is a dopaminergic neurotoxin that displays clinical features of Parkinson's Disease (PD). MPTP leads to the degeneration of nigrostriatal dopaminergic pathway after its systemic administration. Chronic administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 14 publications
1
42
0
4
Order By: Relevance
“…SIRT2 inhibition or deficiency has been shown to produce neuroprotective effects in models of both neurodegenerative diseases [8] and ischemia stroke [9]: SIRT2 inhibition led to a decrease in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal damage [10]; SIRT2 deletion was shown to decrease α-synuclein-induced neurotoxicity in models of Parkinson's disease [11]; SIRT2 inhibitor AK-7 was shown to produce beneficial effects in a mouse model of HD [12]; and SIRT2 deficiency mice also showed decreased neurological deficits after ischemia stroke [9]. However, it is warranted to investigate the mechanisms underlying the neuroprotective effects of SIRT2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT2 inhibition or deficiency has been shown to produce neuroprotective effects in models of both neurodegenerative diseases [8] and ischemia stroke [9]: SIRT2 inhibition led to a decrease in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal damage [10]; SIRT2 deletion was shown to decrease α-synuclein-induced neurotoxicity in models of Parkinson's disease [11]; SIRT2 inhibitor AK-7 was shown to produce beneficial effects in a mouse model of HD [12]; and SIRT2 deficiency mice also showed decreased neurological deficits after ischemia stroke [9]. However, it is warranted to investigate the mechanisms underlying the neuroprotective effects of SIRT2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…This early finding is largely reproduced in more recent findings with other SIRT2 inhibitors in a lactacystin‐induced PD model (Di Fruscia et al, ) and α‐synuclein/MPTP models (Chen et al, ). In fact, SIRT2 knockout mice were also presented with a reduction in MPTP‐induced nigrostriatal damage (Liu et al, ). All in all, there appears to be little doubt that SIRT2 activity could worsen neuronal demise in PD.…”
Section: Connections Between Sirtuins and Pdmentioning
confidence: 99%
“…In any case, resveratrol's sirtuin-activating potential has implicated sirtuins in PD pathology, and over the years many preclinical studies have examined more directly the role of sirtuin paralogues in PD cell and animal models (Outeiro et al, 2007;Chao et al, 2008;van Ham et al, 2008;Albani et al, 2009;Wu et al, 2011;Mud o et al, 2012;Hu et al, 2014;Liu et al, 2014Liu et al, , 2015aLiu et al, , 2015bChen et al, 2015;Di Fruscia et al, 2015;Kitao et al, 2015;Zhang et al, 2016b). The mammalian sirtuin paralogues appear to have conflicting impacts on PD pathogenesis and disease progression.…”
mentioning
confidence: 99%
“…It has been reported that elevation of SIRT2 worsens motor impairment, while inhibition of SIRT2 diminishes striatal DA depletion and improves behavioral abnormalities in rotenone-treated rats [17]. Neurodegeneration induced by a chronic MPTP regimen is prevented by the genetic deletion of SIRT2 in mice [18]. Moreover, the inhibition of SIRT2 in cellular and Drosophila models of PD reduces α-syn-mediated toxicity [19] and also alleviates neuropathology in several models of synucleinopathy by regulating levels of α-syn acetylation, indicating the potential of SIRT2 as a therapeutic intervention for PD by targeting α-syn [20,21].…”
Section: Introductionmentioning
confidence: 99%